The Effect of Abandoned Basic Oxygen Furnace Gas Blowing on the Softening–Melting–Dripping Performance of Full High Cr‐Bearing Vanadia–Titania Magnetite Pellets. Issue 3 (16th December 2019) - Song, Hanlin; Zhang, Jinpeng; Cheng, Gongjin; Yang, Songtao; Xue, Xiangxin
Abstract : It is inevitable to encounter increase in slag thickness, foaming slag, and high iron loss due to excessive formation of titanium carbonitride in blast furnace smelting of full high Cr‐bearing vanadia–titania magnetite (HCVTM). The effects of softening–smelting–dripping properties, the content variation of titanium carbonitride, and mineral element migration process of full HCVTM pellets with abandoned BOF gas (ABOFG) blowing are studied using X‐ray diffraction (XRD), X‐ray fluorescent (XRF), inductively coupled plasma‐atomic emission spectroscopy (ICP‐AES), X‐ray photoelectron spectroscopy (XPS), electron probe microanalysis‐wavelength‐dispersive spectrometer (EPMA‐WDS), and scanning electron microscope‐energy dispersive spectroscopy (SEM‐EDS). ABOFG is a type of neglected byproduct gas resource produced in the steelmaking process with high physical and chemical thermal energies and contains 20–40% CO, 20–30% CO2, 2–5% O2, and 30–50% N2 . As the concentration of CO2 in ABOFG increases, the position and height of the cohesive zone decline, and the concentration of titanium carbonitride decreases from 1.424% to 1.035%, which are beneficial to the BF smelting process. In addition, the migration processes of Ti, V, and Cr are also affected, especially Ti tends to enrich in the dripped slag, whereas V and Cr tend to concentrate at the dripped iron. Abstract : By spraying abandoned BOF gas (ABOFG) into a high Cr‐bearing vanadia–titania magnetite (HCVTM) smelting blast furnace, the CO2 in the ABOFG is used to increase the oxygen potential in the slag–iron interface, suppress the over‐reduction of TiO2, and reduce the formation of TiN. The use of ABOFG improves the high‐temperature performance of HCVTM.